The school experience of descendants of North African immigrants : An entry through the study of the processes of school dropout, ethno-racization and etho-racial discrimination in cycle 3 - (:unkn) unknown (My University, 2021)
Studies about North African immigrants background reveal their school experience is often characterized by low academic children, ethno-racization and ethno-racial discrimination. Despite the presence of risk factors in their life context, some of them have ordinary or even better educational trajectories than ordinary pupils. Therefore, we have chosen an ecosystem approach to try to understand this school experiences diversity. We used a comprehensive qualitative approach to conduct our research with fourteen lower secondary school pupils’ descendants from north African immigrants in the exploratory phase, twenty-seven primary school pupils with at least one North African-born parent, and twenty-seven primary school pupils without direct migratory background in the confirmatory phase. Thanks to the thematic analysis of the testimonies collected, we were able to highlight factors that contribute to building a positive school experience, whose protective effects against a subsequent school dropout are already visible for some of them.
Keywords: African Research